Calcium Channels in Adult Brain Neural Stem Cells and in Glioblastoma Stem Cells - Coronas, Valérie; Terrié, Elodie; Déliot, Nadine; Arnault, Patricia; Constantin, Bruno (Frontiers in Cellular Neuroscience, 2020)
The brain of adult mammals, including humans, contains neural stem cells (NSCs) located within specific niches of which the ventricular-subventricular zone (V-SVZ) is the largest one. Under physiological conditions, NSCs proliferate, self-renew and produce new neurons and glial cells. Several recent studies established that oncogenic mutations in adult NSCs of the V-SVZ are responsible for the emergence of malignant primary brain tumors called glioblastoma. These aggressive tumors contain a small subpopulation of cells, the glioblastoma cancer stem cells (GSCs), that are endowed with proliferative and self-renewal abilities like NSCs from which they may arise. GSCs are thus considered as the cells that initiate and sustain tumor growth and, because of their resistance to current treatments, provoke tumor relapse. A growing body of studies supports that Ca2+ signaling controls a variety of processes in NSCs and GSCs. Ca2+ is a ubiquitous second messenger whose ﬂuctuations of its intracellular concentrations are handled by channels, pumps, exchangers and Ca2+ binding proteins. The concerted action of the Ca2+ toolkit components encodes specific Ca2+ signals with defined spatio-temporal characteristics that determine the cellular responses. In this review, after a general overview of the adult brain NSCs and GSCs, we focus on the multiple roles of Ca2+ toolkit in NSCs and discuss how GSCs hijack these mechanisms to promote tumor growth. Extensive knowledge of the role of Ca2+ toolkit in the management of essential functions in healthy and pathological stem cells of the adult brain should help to identify promising targets for clinical applications.